Enkapsulasi dan Regenerasi Kalus Embriogenik Mangga (Mangifera indica L.) Kultivar Bapang dan Gadung 21 - Tri Muji Ermayanti; Robertus Nugroho; Hamim Hamim (Universitas Atma Jaya Yogyakarta, 2010)
The mother plant and genetic variability of Indonesian mango need to be conserved. Encapsulation is one of in vitro conservation used for many plant species. The aim of this research was to study the regeneration of encapsulated mango cultivar Bapang and Gadung 21 embryogenic callus after storage at -14, 3−5, and 26−27oC for 0, 1, 2, 4, and 8 weeks. Embryogenenic callus was treated with 3% Na-alginate (in liquid 3M), then it was dropped into 100 mM CaCl2. Encapsulated callus beads were dehidrated and stored at -14, 3−5, and 26−27oC for 0, 1, 2, 4, and 8 weeks. After storage, the callus was cultured in 3M medium containing 2,4-D at 0, 1, and 2 mg/l for the regeneration. The results showed that after 8-week storage, callus of Bapang culticar was more viable (67.3%) and resulted more number of somatic embryos (191.6%) than Gadung 21 cultivar. The callus which was cultured in 3M medium without addition of 2,4-D was more viable (20.9%) and had more number of somatic embryos (1062.5%) than that which was cultured on medium containing 2,4-D. After 2-week storage, callus had viability of 7.6%. No storage callus formed more somatic embryos than storage callus. Storage at 26−27oC gave higher viability as well as higher number of somatic embryo than stored at -14 and 3−5 oC. The callus did not regenerate into shoots after storage at -14oC. Embryogenic callus could be stored at 3−5 and 26−27oC for 4 weeks.